(untitled) (Journal of Geography and Environmental Management, 2018)
This article deals with the development of international truism of Great Silk Way and its runs, which go through Kazakhstan. It is not only unique frame of infrastructure, centers and objects of national truism bearing industry. Today the routes of the Great Silk Way which surprisingly correlate with the modern transport system, the system of settling and centers of cultural development are becoming singular bridges between Europe and Asia, the West and the East, but now as the transnational touristic highway. The Great Silk Way made huge role in economic and cultural development of many countries and whole nations, in development whole human being civilization. It is naturally that the Great Silk Way has become the object of Worldwide the heritage of UNESCO. In June 2014, a number of objects – historical monuments along the Silk Road on the Kazakhstan section included at the World Heritage List. In this regard, work has begun on the development of new principles and approaches to the formation and promotion of the tourist product along the entire stretch of historical monuments. In particular, the article describes the activities conducted in the South-Kazakhstan region, where the main objects listed in this list are located.